Exposure of vaccinated and naive cattle to natural challenge from buffalo-derived Theileria parva. Issue 2 (August 2015) - Sitt, Tatjana; Poole, E. Jane; Ndambuki, Gideon; Mwaura, Stephen; Njoroge, Thomas; Omondi, George P.; Mutinda, Matthew; Mathenge, Joseph; Prettejohn, Giles; Morrison, W. Ivan; Toye, Philip
Highlights The Muguga cocktail was tested in cattle in a buffalo-only location. Infection with buffalo-derived T. parva caused Corridor disease in cattle. At the conservancy, the cocktail did not protect cattle against Corridor disease. Efficacious vaccines can support integrative livestock/wildlife management.